Serving Citizens Better : Managing Baghdad's Water Supply and Sewerage with Leadership for Results - Cuvillier, Emmanuel; Mofid, Nafie; Al-Maroof, Salam; Al-Attia, Faris; Randrianarivel, Benjamina; Siddiqi, Najma; Schiffer, Eva; Tsui, Tom (World Bank, Washington, DC, 2014)
Before the Gulf wars, Baghdad had a well-functioning water and sewerage system, with standards of reliability, access, and quality similar to many first world countries, illustrated by a coverage of 95 percent in urban areas and 75 percent in rural areas in the 1990s. Because of the war, economic sanctions, and the deteriorating security situation, the national drinking water coverage was down to 48 percent by 2005. Based on an analysis of the issues, the Mayoralty of Baghdad (MoB) adopted the leadership for results (L4R) approach following contacts with the World Bank team in November 2012. The project "Improving Water and Sewerage Management in Baghdad", supports a change management process in addition to technical infrastructure improvements, and contributes to achieving the government's ambitious goal of serving all citizens of Baghdad with reliable water and sewerage services by 2017 and as outlined in the objectives of the National Development Plan (NDP) 2013-2017. The L4R is about changing behaviors (without large upfront investments) to better serve customers. The L4R and rapid results initiative (RRI) demonstrated that an enabling environment established through leadership, collaborative efforts, and good team dynamics helps to achieve ambitious goals, such as improvements in service delivery, and promote learning, greater accountability, and full ownership of the process involved in reaching a common goal.